A Comparative Study of Berberis aristata D C and Berberis asiatica Roxb ex D C - Mayank Bhatkoti, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
A Comparative Study of Berberis aristata D C and Berberis asiatica Roxb ex D C